Heritability of hemivertebrae in the French bulldog using an animal threshold model. (January 2016) - Schlensker, Eva; Distl, Ottmar
Highlights: Hemivertebrae are widely distributed in French bulldogs. Heritability estimates for the number and grade of hemivertebrae are high. Using dogs with shorter tails as breeding animals may increase the number and grade of hemivertebrae. Breeding measures may be effective in reducing both the number and grade of hemivertebrae. Abstract: Ordinal regression and animal threshold analyses were used to estimate the influence of fixed effects and heritabilities on the number and grade of hemivertebrae, as well as the number of coccygeal vertebrae, in 105 French bulldogs. The fixed effects of sex, year and month of birth were not significant ( P > 0.05). The prevalence of hemivertebrae was 0.85 with a slightly higher prevalence in females compared with males. Heritability estimates for the number and grade of hemivertebrae were 0.58 and 0.53, respectively. The number of coccygeal vertebrae showed a heritability estimate of 0.35. In addition, the number of coccygeal vertebrae was negatively correlated with the number and grade of hemivertebrae. The prevalence of hemivertebrae could increase if dogs with shorter tails are preferentially selected for breeding purposes.